2017
DOI: 10.1158/0008-5472.can-16-2546
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Rationale to Target Highly Expressed CDK7 Conferring Poor Outcomes in Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) patients commonly exhibit poor prognosis and high relapse after treatment, but there remains a lack of biomarkers and effective targeted therapies for this disease. Here, we report evidence highlighting the cell-cycle-related kinase CDK7 as a driver and candidate therapeutic target in TNBC. Using publicly available transcriptomic data from a collated set of TNBC patients ( = 383) and the METABRIC TNBC dataset ( = 217), we found mRNA levels to be correlated with patient prog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 53 publications
3
104
0
Order By: Relevance
“…10,18 In summary, our study showed for the first time that THZ1 may exert its anticarcinogenic effect in HCC cells both in vitro and in vivo in HCC mouse model: (a) inhibiting rapid proliferation of HCC cells; (b) promoting the apoptosis of HCC cells. Thus, THZ1 induced apoptosis by the prolonged CDK7 inhibition in HCC cells.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…10,18 In summary, our study showed for the first time that THZ1 may exert its anticarcinogenic effect in HCC cells both in vitro and in vivo in HCC mouse model: (a) inhibiting rapid proliferation of HCC cells; (b) promoting the apoptosis of HCC cells. Thus, THZ1 induced apoptosis by the prolonged CDK7 inhibition in HCC cells.…”
Section: Discussionmentioning
confidence: 69%
“…5,6 Kwiatkowski et al 7 reported that THZ1 can form a covalent bond by targeting a unique cysteine residue outside the cyclin-dependent kinase 7 (CDK7) kinase domain, which led to the prolonged and irreversible inactivation of CDK7. 7,[9][10][11][12][13] However, no study has been done to explore the possible effects of THZ1 on HCC yet. 8 Moreover, more and more studies illustrated that THZ1 exhibited encouraging therapeutic effects in different tumor types, such as small cell lung cancer, T-ALL, triple-negative breast cancer, ovarian cancer, and high-grade glioma.…”
mentioning
confidence: 99%
“…Both THZ1 and BS-181 HCl specifically target CDK7. Nevertheless, Patient #1 PDTOs showed a strong response to the former but no response to the latter which could be attributed to the different activity of the two as recently observed in breast cancer 28 .…”
Section: Patient #1: High-grade Mixed Type Carcinomamentioning
confidence: 66%
“…Numerous cancers appear to be dependent on elevated CDK7 activity to drive their oncogenic state . Because of its role in cell cycle regulation, CDK7 activity cannot be entirely de‐coupled from its broad transcriptional effects.…”
Section: Pathologies Associated With Tfiih Functionmentioning
confidence: 99%
“…Numerous cancers appear to be dependent on elevated CDK7 activity to drive their oncogenic state. 192,193 Because of its role in cell cycle regulation, CDK7 activity cannot be entirely de-coupled from its broad transcriptional effects. However, elevated expression of oncogenes is enabled by clusters of enhancers, or super-enhancers, [194][195][196] that require CDK7 activity to maintain their high-level expression.…”
Section: Cancermentioning
confidence: 99%